Pengaruh Model Pembelajaran Kooperatif Think-Pair-Share Berbantuan Kartu Uno Terhadap Pemahaman Konsep Perkalian Siswa Kelas III di SDN Susukan 03 Pagi - Rizqi, Sendy Annafi; Kasriman, Kasriman (Jurnal Ilmiah Global Education, 2025)
This research aims to analyze the influence of the Think-Pair-Share (TPS) cooperative learning model combined with Uno Multiplication Cards on the multiplication concept understanding of third-grade students at SDN Susukan 03 Pagi. The problem addressed is the low mathematics learning outcomes of students, specifically in multiplication, and the minimal use of innovative and interactive teaching methods. The research used a quantitative approach with a Pretest-Posttest Nonequivalent Control Group design, involving 63 students who were divided into an experimental group (TPS + Uno Cards) and a control group (conventional learning). The t-test results revealed a significant difference between the two groups (p-value 0.000), with the experimental group's posttest average score increase being higher than the control group's. The N-Gain analysis indicates moderate effectiveness (0.4678) for the experimental class and low effectiveness (0.1535) for the control class. This finding proves that combining the TPS model with Uno Multiplication Cards is effective in improving students' understanding of multiplication concepts and actively and enjoyably engaging them. This research recommends implementing this method in mathematics learning to strengthen students' learning outcomes as well as their social skills.